Isogeometric boundary element method for the simulation of underground excavations. Issue 3 (30th September 2013) - Beer, G.; Duenser, C.; Marussig, B.
Abstract : Isogeometric methods have become the latest trend in numerical simulation. Their attractiveness stems from the fact that the description of the geometry can be taken directly from CAD programs, avoiding the need for mesh generation. Since NURBS (non-uniform rational B-splines) functions that exhibit desirable properties such as high continuity and efficient refinement algorithms are also used for the description of the unknowns, a higher quality of results can be expected. This paper presents some results from the research project 'Fast isogeometric boundary element methods for tunneling'. The aim of the project is to implement a fast and accurate method for the simulation of underground excavations without the need for the generation and subsequent refinement of a mesh.